2019
DOI: 10.14744/anatoljcardiol.2019.66805
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of left ventricular function in type 2 diabetes mellitus patients with non-alcoholic fatty liver disease by three-dimensional speckle tracking echocardiography

Abstract: The Anatolian Journal of Cardiology is an international monthly periodical on cardiology published on independent, unbiased, double-blinded and peerreview principles. The journal's publication language is English however titles of articles, abstracts and Keywords are also published in Turkish on the journal's web site.The Anatolian Journal of Cardiology aims to publish qualified and original clinical, experimental and basic research on cardiology at the international level. The journal's scope also covers edit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
0
8
0
2
Order By: Relevance
“…This indicated that longitudinal strain was more susceptible to change than circumferential strain in the LV of patients with diabetes. It is possible that the LV endocardium, the myocardial fibers of which are predominantly distributed longitudinally, is the first to be damaged by hyperglycemia or free fatty acids, which endows the longitudinal strain with higher statistical significance than circumferential strain 28 . This result is consistent with the reported findings of many previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that longitudinal strain was more susceptible to change than circumferential strain in the LV of patients with diabetes. It is possible that the LV endocardium, the myocardial fibers of which are predominantly distributed longitudinally, is the first to be damaged by hyperglycemia or free fatty acids, which endows the longitudinal strain with higher statistical significance than circumferential strain 28 . This result is consistent with the reported findings of many previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…A 2019 meta-analysis of 16 observational studies further confirmed that NAFLD (as detected by imaging techniques or liver biopsy) was independently associated with many functional and structural myocardial abnormalities, including higher left ventricle mass, higher left ventricular end diastolic diameter, higher left atrium diameter and the ratio between left atrial volume and body surface area, higher posterior wall and septum thickness, lower E/A wave ratio, higher E/E ratio, longer deceleration time and longer relaxation time [58]. Interestingly, recent observational studies also indicated that NAFLD (as detected by ultrasonography) was associated with a reduction in global longitudinal strain, which is a relatively novel echocardiographic parameter strongly associated with adverse cardiovascular outcomes [59][60][61]. NAFLD was associated with an increased risk of incident CKD (random-effects hazard ratio 1.43, 95% confidence interval 1.33-1.54)…”
Section: Sub-clinical Myocardial Remodelling and Dysfunction Heart Va...mentioning
confidence: 99%
“…This forms a basis for the importance of cardiac assessment in diabetic patients with moderate to severe NAFLD to allow early clinical intervention and treatment. 82 LV remodeling and hypertrophy are complications seen in diabetic patients and were suggested to have a causative contribution to GLS reduction. 83 …”
Section: Speckle Tracking Echocardiographymentioning
confidence: 99%